Self-References in English Press Releases of Indonesian Coal Mining Companies - Emma Natasha Octoveria; Tofan Dwi Hardjanto (Universitas Gadjah Mada, 2022)
Corporate press release is a pivotal public relation tool, especially for those operating on a mass scale and have high risks, such as for coal mining companies. They are aimed to effectively function in both maintaining a good public image and minimize public backlash regarding companies’ operation. Considering the importance of press releases, how companies employ careful linguistic choices in press releases is worth exploring. One of the aspects to analyze is the use of self-references, in both forms and the use. In this research, the forms of self-references in corporate press releases are investigated. The metadiscourse functions of self-references employed in their press releases also become matters of discussion. The data were obtained from English press releases of two Indonesian coal mining companies, PT Adaro Energy Tbk (Adaro) and PT Bumi Resources (Bumi) from the year 2019 to 2020. These data were quantitatively analyzed with a concordance software named WordSmith Tool (Scott, 2004) that enables a concordance feature to discover the frequencies of self-references used by Adaro and Bumi in their press releases. To discover the use of self-references used by Adaro and Bumi in their press releases, a qualitative analysis was conducted. Specifying on the metadiscourse functions, a taxonomy of writer-reader interactions by Adel (2006) was employed. The result shows that forms of self-references in press releases of Adaro and Bumi are different, despite both operating under the same industry. Moreover, it is discovered that different forms of self-references in press releases are used differently in metadiscourse functions.